Giant enhancement of inverted polymer solar cells efficiency by manipulating dual interlayers with integrated approaches. Issue 2 (2nd December 2014) - Hsieh, Hsing-Hua; Sung, Yun-Ming; Hsu, Fang-Chi; Hsiao, Kuo-Jui; Lee, Ya-Ju; Chen, Yang-Fang
Abstract : Interlayer properties play an important role in governing the charge collection efficiency of polymer solar cells. Abstract : Interlayer properties play an important role in governing the charge collection efficiency of polymer solar cells. We report a giant enhancement of light harvesting based on the integration of different concepts to manipulate the cathode and anode interlayers in an inverted ITO/ZnO-nanorod/poly(3-hexythiophene):(6, 6)-phenyl C61 butyric acid methyl ester (P3HT:PCBM)/poly(3, 4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS)/Ag cell structure. A layer of conjugated small molecules is self-assembled on the front cathode interlayer while gold nanoparticles are doped into the rear anode interlayer. The former one carries the characteristic of surface passivation and the latter one has the unique property of localized surface plasmon effect. Quite interestingly, both approaches can effectively enhance the exciton dissociation rate and extend the carrier lifetime. Through the integrated approaches in a single cell, by taking the advantage of each individual contribution and the coupling effect between them, the efficiency can be further boosted from 2.02% to 4.36%, which sets the record for the inverted polymer solar cell using ZnO-nanorod as electron transporting layer and P3HT:PCBM as photoactive layer so far.